The Influence Of Work Stress And Skills On Employee Work Performance At The Lahat Regency Education Office - Titi Hasanah; Herliansyah Herliansyah (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine how the influence of work stress and skills partially and simultaneously affect the work performance of employees at the Regional Secretariat of Lahat Regency. The sample in this study was 57 respondents. The sampling method used by the researcher was Incidental sampling. This type of research is quantitative research using multiple linear regression analysis techniques processed using the SPSS application and produces a regression equation. The results of this study are: there is a significant influence between work stress on the work performance of employees at the Regional Secretariat of Lahat Regency, there is a significant influence between work skills on the work performance of employees at the Regional Secretariat of Lahat Regency. The F test shows that work stress and skills have a simultaneous effect on the work performance of employees at the Lahat Regency Education Office.